COOKING ACADEMY 2 WORLD CUISINES AS A TOOL FOR IMPROVING SPEAKING ABILITY - Kusuma, Adie Wirahadai (2012)
The study entitled "Cooking Academy 2 World Cuisines as a Tool for Improving Speaking Ability". It is proposed to investigate the use of playing computer-based cooking game on students' speaking ability mastery. The research questions are addressed to find out whether this activity can be used in the speaking class or not. The study used pre-test, post-test, and structured questionnaire to answer the research questions. Data were taken by means of an instrument, involving twenty five students in one of SMA Pariwisata in Bandung. Both data were analyzed by SPSS statistics 17.0 for windows. The result score is assessed in three aspects; fluency, pronunciation, and discourse management. The study reveals that experimental and control classes improved by 19.909: 5.209, the experimental class' score highly improved than control class. It is also found that most of participants improve their speaking ability by the game. This study can be used as an input to improve the students' speaking ability in learning procedure text.